Geotechnical investigation of low-plasticity organic soil treated with nano-calcium carbonate - O'Kelly, Brendan (My University, 2023)
Soil stabilization using nanomaterials is an emerging research area although, to date, its investigation has mostly been laboratory-based and therefore requires extensive study for transfer to practical field applications. The present study advocates nano-calcium carbonate (NCC) material, a relatively unexplored nanomaterial additive, for stabilization of low-plasticity fine-grained soil having moderate organic content. The plasticity index, compaction, unconfined compressive strength (UCS), compressibility and permeability characteristics of the 0.2%, 0.4%, 0.6% and 0.8% NCC-treated soil, and untreated soil (as control), were determined, including investigations of the effect of up to 90-d curing on the UCS and permeability properties. In terms of UCS improvement, 0.4% NCC addition was identified as the optimum dosage, mobilizing a UCS at 90-d curing of almost twice that for the untreated soil. For treated soil, particle aggregation arising from NCC addition initially produced an increase in the permeability coefficient, but its magnitude decreased for increased curing owing to calcium silicate hydrate (CSH) gel formation, although still remaining higher compared to the untreated soil for all dosages and curing periods investigated. Compression index decreased for all NCC-treated soil investigated. SEM micrographs indicated the presence of gel patches along with particle aggregation. X-ray diffraction (XRD) results showed the presence of hydration products, such as CSH. Significant increases in UCS are initially attributed to void filling and then because of CSH gel formation with increased curing.
PUBLISHED
Keywords: Organic silt; Calcium carbonate; Nano-calcium carbonate (NCC); Calcium silicate hydrate (CSH); Soil stabilization; Smart & Sustainable Planet; CALCIUM-CARBONATE; GEOTECHNICAL ENGINEERING; Geotechnics; Ground improvement; NANO PARTICLES; NANOPARTICLES; Nano-Materials; Nanomaterials; Nanoparticle; Nanotechnology; Organic soil; SOIL MODIFICATION; Soil Mechanics; Soil Mechanics & Foundations; geotechnical